Educating emergency department nurses about trauma informed care for people presenting with mental health crisis: a pilot study. Issue 1 (December 2016) - Hall, Andrea; McKenna, Brian; Dearie, Vikki; Maguire, Tessa; Charleston, Rosemary; Furness, Trentham
Abstract Background Practicing with trauma informed care (TIC) can strengthen nurses' knowledge about the association of past trauma and the impact of trauma on the patient's current mental illness. An aim of TIC is to avoid potentially re-traumatising a patient during their episode of care. A TIC education package can provide nurses with content that describes the interplay of neurological, biological, psychological, and social effects of trauma that may reduce the likelihood of re-traumatisation. Although mental health nurses can be TIC leads in multidisciplinary environments, the translation of TIC into clinical practice by nurses working in emergency departments (EDs) is unknown. However, before ED nurses can begin to practice TIC, they must first be provided with meaningful and specific education about TIC. Therefore, the aims of this study were to; (1) evaluate the effectiveness of TIC education for ED nursing staff and (2) describe subsequent clinical practice that was trauma informed. Methods This project was conducted as exploratory research with a mixed methods design. Quantitative data were collected with an 18-item pre-education and post-education questionnaire. Qualitative data were collected with two one-off focus groups conducted at least three-months after the TIC education. Two EDs were involved in the study. Results A total of 34 ED nurses participated in the TIC education and 14 ED nurses participated in the focus groups. There was meaningful change (p  < 0.01, r  ≥ 0.35) in 9 of the 18-items after TIC education. Two themes, each with two sub-themes, were evident in the data. The themes were based on the perceived effectiveness of TIC education and the subsequent changes in clinical practice in the period after TIC education. Conclusion Emergency department nurses became more informed of the interplay of trauma on an individual's mental health. However, providing care with a TIC framework in an ED setting was a considerable challenge primarily due to time constraints relative to the day-to-day ED environment and rapid turnover of patients with potentially multiple and complex presentations. Despite this, nurses understood the effect of TIC to reduce the likelihood of re-traumatisation and expressed a desire to use a TIC framework.